Local elections 2000: analyzing the results of the elections - Lukošaitis, Alvidas (Politologija, 2000)
In this article the focus is given to analyzing the results of Local elections, fluctuations of the party electorate and the major changes in the party system as driven by the former. The results of last three Local elections (as of 1995, 1997 and 2000) are posted to comparison. Not a few statistical data is presented in the work. Author postulates that the elections have elucidated the processes ongoing in the party system and the leaders of the political powers. In the face of the upcoming Seimas elections, the results of the elections become the fact attracting special importance. It is said that in the aftermath of 1995, 1996 and 1997 elections the power pendulum shifts gradually from the right-wing to the left-wing forces. The author observes that the ever-sharpening competition between the parties and the displacement of powers makes parties not only look for new efforts to survive but also to endorse and revise the democratic values all over again. The article consists of the following chapters: I. Three Local Elections: Comparative Statistics; II. Forecasting, Evaluating and Commenting the Results of the Elections; III. Several Peculiarities of the Elections Campaign; IV. Influence of the Electoral Dynamics upon the Development of the Party System; V. Following Local Elections for Seimas Elections: The Results of the Elections as an Indicator of the Processes Ongoing in the Party System. The Local elections as of March 2000 are not the first in Lithuania. Democracy has become the "single game in the yard." In comparison to 1997 elections the parties were better prepared to participate in these elections, the campaign was more lively, kaleidoscopic and pithy. On the other hand, it is obvious that most of the parties had but limited resources to carry out effective election campaigns, first of all because of the lack of finances and the people, who understand the process of elections professionally. Besides, the elections were held during a difficult situation characterized by sudden and very dynamic changes within the party system. The parties had to attract and persuade people, and the people had to choose whom to vote for, at the time when confidence in the parties fell into decay, they faced devaluation and internal partitions. In addition, the elections faced difficult economic, social conditions. Lack of confidence in politics and the Government were high before the elections. In part, the results of the elections explain some of the consequences of such a situation - crystallization of favorable grounds in Lithuania for radical sentiments, which have little rational argument at their core. In part I of the article the author reaches such conclusions: from 1995 up till 2000 30 parties have participated in Local elections. Second, none of the parties established after 1995 achieved somewhat successful results, oftentimes they scored in the second or the third tenth. Third, around ten parties share among themselves the bulk of mandates. Fourth, these elections illustrated that no dominant party is left. In part II of the article the author tends to discuss forecasts that were presented before the elections, evaluations and comments of the elections as depicted in their aftermath. Reasons why the forecasts failed to correspond to outcomes are given. It is said that the first evaluations of the elections were unilateral - namely, forecasts of specialists and experts (political scientists, sociologists) failed to predict the outcomes of the elections. Only with time to pass did everyone pay attention to the fact that none spoke of the way mandates will be distributed among the parties. It came to be noted that surveys carried by sociologists were oriented as always to finding attitudes of the voters. These attitudes then were the basis upon which the distribution and number of mandates was counted. Second, questions as given in the surveys were not "dedicated" clearly to Local elections (i.e., "If elections to Seimas were held tomorrow, what party would you vote for?"). Third, sociological surveys were held two and three weeks ahead of the elections. However, they were published with one week left. Fourth, forecasts made by political scientists are most often related to analyzing and forecasting changes the results of the elections might bring with respect to relations, interaction and composition of political forces within the party system. In part III of the article the author elucidates several peculiarities of the past Local elections campaign. According to the author, increased attention to the formation of candidates’ lists is one of the peculiarities. The lists were viewed more scrupulously by the Supreme Elections Commission, State Security Department expressed its opinion with regard to the issue. Another peculiarity concerns the methods of the campaign itself. Like never before did the parties try to "embellish" their list with well-known personalities, which are new, however, not alien to politics. High number of Seimas deputies attended the Local elections campaign. All this contributed to making the elections campaign more lively and colorful. Like never before the media and public paid much attention to the issue of party financing, to the question of relations between the political parties and the interest groups. All the above mentioned might have had influence on the following peculiarity - in comparison to previous elections, voters were much more active. However, the author adds, too little attention was given by the parties to principal questions, programmatic provisions. Albeit, several parties (Conservatives (TS/LK), Socialdemocrats (LSDP), Labour party (LDDP), Centre Union (LCS), Liberals (LLS), New Union/Socialliberals (NS/SL), etc.), in the opinion of the author, had rather-solidly-prepared programs. Author identifies the way parties tend to evaluate the results of Local elections and major changes driven by these. These major changes relate, first, to changes within the contingent of the party-supporting franchise. One of the most important factors once assuring the stability of Lithuania’s party system falls into decay - namely, the continuity of party electorate. With this, the second major change is bound - the Local elections have given birth to the most radical changes in the Party system since the beginning of its formation. Primary consequence of the changes - intensified rotation of the leaders and sharpened party competition, the second-hand consequence - a very different party behavior, motivated, literally, by the very need to survive. The most tangible criterion of these processes is illustrated by rapprochement of ideologically familiar and imminent parties and by the inception of coalition politics. Analyzing the party behavior after the elections allows one to expect that notwithstanding prior situation in Lithuania these processes would become reality for the first time. Besides, the ability of the parties to coordinate common policy, their coalition cooperation is treated to be a strong indicator of their capacity to compete. Author suggests the proposition that after the Local elections Lithuania’s party system has in qualitative sense entered a new stage of its development. Rotating the party leaders, revising programmatic provisions to give up declarative principal differences (universalization), ever intensifying control of the party elite, attempting to transfer higher level of responsibility from center to periphery (branches), accentuating new responsibilities to the electorate - all these tendencies contribute to confirm the proposition. This is neither good, nor bad - given constant improvement of the internal party organization and the mutual interactions, this is inevitable. Author claims that the entire problem is tied to the fact that these processes are all rather complicated. They ask for much attention to be paid at the time when little time is left to reaching Seimas elections.